2016
DOI: 10.1002/app.44129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the emulsion copolymerization of vinyl pivalate and methacrylated methyl oleate

Abstract: In this study, we synthesized a new class of copolymeric lattices based on vinyl pivalate (VPi) and modified oleic acid (OA) through a batch emulsion polymerization process. The effects of the chemically modified OA [methacrylated methyl oleate (MAMO)] on the thermal stability, glass‐transition temperature (Tg), average molar masses [mass‐average molar mass (Mw) and number‐average molar mass (Mn)], and molar mass dispersity (Ð) of the copolymers were evaluated. The experimental results indicate that via the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The second significant weight loss observed (420–520 °C) is resultant of polymeric chains with an elevated concentration of AFAME. It is worth mentioning that the thermal stability of poly(styrene‐ co ‐AFAME) in comparison to polystyrene has decreased with increasing of AFAME concentration in the reaction medium …”
Section: Resultsmentioning
confidence: 99%
“…The second significant weight loss observed (420–520 °C) is resultant of polymeric chains with an elevated concentration of AFAME. It is worth mentioning that the thermal stability of poly(styrene‐ co ‐AFAME) in comparison to polystyrene has decreased with increasing of AFAME concentration in the reaction medium …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the 1 H-NMR spectrum of the mixture of fatty acids of soybean oil and the products of each modification step: epoxidation and acrylation. In the fatty acid spectrum (Figure 1a), a signal δ = 5.3 ppm is observed, characteristic of hydrogens attached to unsaturated carbons (H1 and H2, corresponding mainly to linolenic, linoleic and oleic acids), confirming the presence of double bonds in the chemical structure of the fatty acids [27]. After the epoxidation step, a reduction in the intensity of these signals is observed with the appearance of two signals at δ = 3.1 ppm and δ = 2.9 ppm, characteristic of hydrogens bonded to the carbon of the epoxide ring (H1 and H2).…”
Section: Modification Of Soybean Oilmentioning
confidence: 76%
“…When the methacrylic acid was replaced by the acrylated fatty acid mixture, a decrease in the glass transition temperature of the material with increasing fatty acid fraction was observed. In previous works, Jensen and collaborators observed that the incorporation of acrylated fatty acid into the polymer chain reduced the glass transition temperature of the copolymers [18,27]. Figure 4 shows the 1 H-NMR spectra of poly(methyl methacrylate-co-vinyl pivalate)-TAFA5_d and TAFA10_d polymer samples-evidencing the characteristic peaks of VPi (4.5-5.0 ppm), MMA (3.5 ppm), and AFA (2.3 ppm).…”
Section: Emulsion Polymerizationmentioning
confidence: 98%
See 1 more Smart Citation
“…As a matter of fact, a very stable colloidal dispersion is generally obtained through ultrasonication or high shear devices that might be combined with a surfactant and a hydrophobic agent, which acts as a costabilizer in order to lead to the formation of droplets lying in the interval from 50 to 500 nm, exhibiting very narrow particle size distributions. Generally, highpressure homogenizers or sonicators are necessary when the formation of nanometric droplets requires a large amount of energy, which results from the application of high shear rates on the oil-in-water medium, leading efficiently to the breakage of the larger droplets to produce small droplets [217][218][219][220][221][222][223].…”
Section: Emulsification and Solvent Evaporationmentioning
confidence: 99%